The critical implications of Ubuntu for contemporary management theory - Mashasha, Tamsanqa Munyaradzi (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2014)
Since the dissolution of apartheid, corporate governance in South Africa has evolved from being a soft mainly ethical issue to a hard knowledge-based technological issue, recognised as pivotal to the success and revitalisation of the country's capital markets and, ultimately, the prospects of the corporate economy. These high stakes have produced a succession of measures aimed at transforming corporate governance in the economy. As such, South Africa's corporate managers are consistently faced with the seemingly unassailable obstacle of discerning and implementing technologically progressive and culturally/racially unbiased management strategies/systems. The focus of this thesis is the latter of these two obstacles. Ubuntu acts as the scope via which the issues embedded within the incumbent management strategies/systems are viewed. Ubuntu philosophy embodies a socio-cultural framework that applies to all individuals and institutions throughout the continent. It embodies collectivism and teamwork, creation of synergies and competitive advantages, humanist leadership styles and maturity, consensus in decision-making systems, effective communication, and community-based corporate social responsibility. Ubuntu is pervasive in almost all parts of Southern African continent "“ it is integrated into all aspects of day-to-day life throughout the region. This thesis reviews and analyses some of the lessons that can be learned through the inception of African management, more specifically Ubuntu management, within South Africa's corporate sphere. This thesis aims to prove that there exists a need for a new South African corporate management system, one which is able to harmoniously integrate the incumbent, western-orientated management strategies and systems with one of African origins.
Keywords: Management -- Africa -- Philosophy; Ubuntu (Philsophy); Corporate governance -- South Africa; Management -- South Africa